Standardizing the morbidity and mortality conference and utilizing it as a tool for education and quality improvement: One program's experience - C U Aneji; S M Lopez (International Journal of Medicine and Health Development, 2017)
The morbidity and mortality conference (MMC) offers an opportunity to incorporate principles of quality improvement and patient safety, with the potential to improve patient outcomes, while providing a rich opportunity to teach. However, the format of the conference varies tremendously among academic programs, and the goals of the conference are often not clearly defined. The cases presented also vary tremendously. The goal was to move the MMC at our institution beyond an autopsy and clinical case review to a comprehensive model aimed at improving the quality and safety of care provided and improving of the quality of education at an academic medical institution. The conference is a core requirement of the neonatal-perinatal medicine fellows' education at our institution. Previously there was passive learner involvement. We implemented structured changes to the process of case selection, preparation and presentation utilizing patient selection guidelines, an adapted worksheet for critically analyzing the case and a PowerPoint presentation template which includes a clear outline with objectives. This has resulted in uniformity in the format and content of our MMC and has created a vehicle for identifying areas of weaknesses in our practice and system leading to quality improvement initiative projects aimed at improving the quality and safety of the care delivered to our patients. This paper details the evolution process of the MMC at our academic institution and describes the structured changes implemented, their impact and lessons learned.